PENDIDIKAN DAN INOVASI SEBAGAI PILAR PEMBANGUNAN EKONOMI DALAM UPAYA MENINGKATKAN KUALITAS SDM DI INDONESIA - Diki Aditia Pratama; Iin Khairunnisa (Educatus, 2025)
Education and innovation are two strategic pillars in supporting economic development and improving the quality of human resources (HR) in Indonesia. Amidst the challenges of globalization, the industrial revolution 4.0, and the dynamics of digital transformation, Indonesia still faces a number of fundamental problems, such as inequality in access and quality of education, low relevance of the curriculum to industry needs, and a weak research and innovation culture in both academic and business environments. Although the government has issued various strategic policies, such as the Independent Curriculum, strengthening vocational education, and establishing the National Research and Innovation Agency (BRIN), the implementation of these policies has not been fully effective in addressing existing structural and systemic challenges. This study aims to analyze the role of education and innovation in building superior HR that can contribute to national economic growth. A descriptive qualitative approach is used to examine various government policies and their impact on HR development, by referring to secondary data and recent literature studies. The results of the study indicate that stronger synergy between the education sector, government, and industry is needed to create a sustainable innovative ecosystem. In addition, restructuring education policies based on local needs, improving the competence of educators, and providing incentives for innovation are the keys to accelerating the realization of productive and globally competitive HR. By strengthening the pillars of education and innovation, Indonesia can achieve inclusive and sustainable economic growth towards the vision of Golden Indonesia 2045.